Pengembangan Android-based Interactive Mobile Learning dengan Model Guided Inquiry Learning untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi pada Materi Gelombang Cahaya - Siti Meisaroh; Suparno (Postgraduate, University of Mataram, 2024)
This research aims to produce Android-based interactive mobile learning with a guided inquiry model of light wave material that is able to improve students' HOTS abilities. This research is a 4D model type research. The research was conducted at MAN 1 Ponorogo, MAN 2 Ponorogo, and SMAN 1 Badegan. The research subjects were 149 class XI MIPA students who gave a pretest-posttest. Student pretest-posttest data were analyzed using 1-way ANOVA to determine the differences in students' HOTS skills in the control and experimental classes. Based on the 1-way ANOVA test, it was found that there were differences in students' HOTS abilities in the two classes. Classes that use Android-based interactive car learning get higher results compared to classes that don't use Android-based interactive car learning.